Extent of disease activity assessed by 18F-FDG PET/CT in a Dutch sarcoidosis population - Cremers, Johanna P; Van Kroonenburgh, Marinus J; Mostard, Rémy L; Vöö, Stefan A; Wijnen, Petal A; Koek, Ger H; Drent, Marjolein (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2014)
Background Sarcoidosis is characterized by a wide range of disease manifestations. In the management and follow-up of sarcoidosis patients, knowledge of extent of disease, activity and severity is crucial. Objectives The aim of this study was to assess the extent, distribution and consistency of inflammatory organ involvement using 18F-FDG PET/CT (PET) in sarcoidosis patients with persistent disabling symptoms. Methods Retrospectively, sarcoidosis patients who underwent a PET between 2005 and 2011 (n=158) were included. Clinical data were gathered from medical records and PET scans were evaluated. Positive findings were classified as thoracic and/or extrathoracic. Results Of the studied PET positive sarcoidosis patients (n=118/158; 75%), 93% had intrathoracic activity (79% mediastinal and 64% pulmonary activity, respectively) and 75% displayed extrathoracic activity (mainly peripheral lymph nodes, bone/bone marrow, and spleen). Hepatic positivity was always accompanied by splenic activity, whereas the majority of patients with parotid gland, splenic or bone/bone marrow activity showed lymph node activity. A substantial number of patients with PET positive pulmonary findings (86%) had signs of respiratory functional impairment. No obvious association between hepatic, splenic or bone/bone marrow activity and their corresponding laboratory abnormalities suggestive of specific organ involvement, was found. Conclusions The majority of studied patients appeared to have PET positive findings (75%), of which a high proportion (75%) displayed extrathoracic activity. Hence, PET can be especially useful in the assessment of extent, distribution and consistency of inflammatory activity in sarcoidosis to provide an explanation for persistent disabling symptoms and/or to provide a suitable location for biopsy.